2019
DOI: 10.1186/s40885-019-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body mass index and its interaction with family history on hypertension: a case–control study

Abstract: Background BMI is an indicator commonly used in the world to measure the weight and height of the body, it reflects the comprehensive outcome of acquired lifestyle; FH is a sign reflecting the main role of genetic factors. This study aimed to evaluate the effect of BMI and interaction with FH on hypertension risk in Shanghai adult population. Methods According to l:l matched pairs design, 342 cases and 342 controls were selected and investigated in this study, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
2
18
0
2
Order By: Relevance
“…It's well known that the genetic factors play an important basic role in the occurrence of hypertension, and family history is a sign reflecting the main role of genetic factors. It's showed that family history plays an important role in the development of hypertension through interaction with acquired risk factors such as body mass index (BMI), and the interaction of family history and BMI is greater than the sum of two independent actions [24][25][26][27][28]. In this study, the genetic epidemiological results showed that the prevalence of hypertension in three degree relatives was different.…”
Section: Discussionmentioning
confidence: 82%
“…It's well known that the genetic factors play an important basic role in the occurrence of hypertension, and family history is a sign reflecting the main role of genetic factors. It's showed that family history plays an important role in the development of hypertension through interaction with acquired risk factors such as body mass index (BMI), and the interaction of family history and BMI is greater than the sum of two independent actions [24][25][26][27][28]. In this study, the genetic epidemiological results showed that the prevalence of hypertension in three degree relatives was different.…”
Section: Discussionmentioning
confidence: 82%
“…It is well known that the genetic factors play an important basic role in the occurrence of hypertension, and family history is a sign reflecting the main role of genetic factors. It's showed that family history plays an important role in the development of hypertension through interaction with acquired risk factors such as body mass index (BMI), and the interaction of family history and BMI is greater than the sum of two independent actions [23]. In this study, the genetic epidemiological results showed that the prevalence of hypertension in three degree relatives was different.…”
Section: Discussionmentioning
confidence: 75%
“…It is well known that the genetic factors play an important basic role in the occurrence of hypertension, and family history is a sign reflecting the main role of genetic factors. It's showed that family history plays an important role in the development of hypertension through interaction with acquired risk factors such as body mass index (BMI), and the interaction of family history and BMI is greater than the sum of two independent actions [22]. In this study, the genetic epidemiological results showed that the prevalence of hypertension in three degree relatives was different.…”
Section: Discussionmentioning
confidence: 75%